2017
DOI: 10.1167/iovs.17-22587
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Mydriasis-Free Flicker ERGs Recorded With Real-Time Correction for Retinal Illuminance: Study of 150 Young Healthy Subjects

Abstract: These results indicate that the fundamental components of the RETeval flicker ERGs are significantly affected by the axial length, pupillary area, and sex of young healthy subjects. The results also suggest that it would be better to compensate for the Stiles-Crawford effect when flicker ERGs are recorded with natural pupils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
3
24
5
Order By: Relevance
“…At 14 years of age, BCVA decreased to 0.05 in each eye. Electroretinography (ERG) with skin electrodes was performed using the RET eval system (LKC Technologies, Gaithersburg, MD) as previously described (Kato et al, 2017), which showed that the light‐adapted 30‐Hz flicker response was non‐recordable (Figure 1c). At this time, he was ophthalmologically diagnosed with progressive retinal dystrophy such as retinitis pigmentosa, in addition to optic disc atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…At 14 years of age, BCVA decreased to 0.05 in each eye. Electroretinography (ERG) with skin electrodes was performed using the RET eval system (LKC Technologies, Gaithersburg, MD) as previously described (Kato et al, 2017), which showed that the light‐adapted 30‐Hz flicker response was non‐recordable (Figure 1c). At this time, he was ophthalmologically diagnosed with progressive retinal dystrophy such as retinitis pigmentosa, in addition to optic disc atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Flicker ERGs were recorded three times from both eyes with the RETeval® system (Mayo, Inazawa, Japan); the first recording was made before the injection of an anti-VEGF agent (Phase 1), the second was within 2 hours after the injection (Phase 2), and the third was 2 to 24 hours after the injection (Phase 3). The components of the RETeval system have been described in detail [21,24,25,27].…”
Section: Methodsmentioning
confidence: 99%
“…Flicker ERGs were recorded three times from both eyes with the RETeval® system (Mayo, Inazawa, Japan); the first recording was made before the injection of an anti-VEGF agent (Phase 1), the second was within 2 hours after the injection (Phase 2), and the third was 2 to 24 hours after the injection (Phase 3). The components of the RETeval system have been described in detail [21,24,25,27]. recording.…”
Section: Methodsmentioning
confidence: 99%